(untitled) (Journal of Atomic and Molecular Sciences, 2015)
An algebraic method is proposed to generate a self-consistent converged complex polarizability of atoms and molecules from limited available data. An iterative method is also suggested to generate the general accurate local field models of condensed systems. The effect of the local fields on the photoabsorption cross sections as the functions of the media density and structures has been studied in the present work. A substantial influence on the photoabsorption cross section has been found when the media density exceeds a critical density in the present unique model.